Pricing options with stochastic volatility model. - Lee, Sor Hong. (2008)
The purpose of this thesis is to review the evidence of non-constant volatility and to consider the implications for option pricing using stochastic volatility model. We concentrate on the Stochastic Volatility Model developed by Steven L. Heston in 1993 as it processes a closed-form formula that is practically implementable.